Reproductive phenology of two Mimusops species in relation to climate, tree diameter and canopy position in Benin (West Africa). (21st November 2017) - Sinasson Sanni, Gisèle K.; Shackleton, Charlie M.; Sinsin, Brice
Abstract: Assessing species phenology provides useful understanding about their autecology, to contribute to management strategies. We monitored reproductive phenology of Mimusops andongensis and Mimusops kummel, and its relationship with climate, tree diameter and canopy position. We sampled trees in six diameter classes and noted their canopy position. For both species flowering began in the dry season through to the rainy season, but peaked in the dry season, whilst fruiting occurred in the rainy season and peaked during the most humid period. Flowering was positively correlated with temperature. Conversely, fruiting was negatively correlated with temperature and positively with rainfall, only in the Guineo‐Sudanian zone. For M . andongensis, flowering and fruiting prevalences were positively linked to stem diameter, while only flowering was significantly related to canopy position. For M . kummel, the relationship with stem diameter was significant for flowering prevalence only and in the Guineo‐Sudanian zone. Results suggest that phylogenetic membership is an important factor restricting Mimusops species phenology. Flowering and fruiting of both species are influenced by climate, and consequently climate change might shift their phenological patterns. Long‐term investigations, considering flowering and fruiting abortion, will help to better understand the species phenology and perhaps predict demographic dynamics.